Chickpea genotype resistance to Meloidogyne javanica and Pratylenchus brachyurus in field conditions - Santos, Leidiane Pinheiro dos; Pereira, Wellington José; Silva, Débora Zacarias da; Gonçalves, Daniel José; Alves, Gleina Costa Silva; Pinheiro, Jadir Borges; Silva, Giovani Olegario da; Melo, Raphael Augusto de Castro e; Nascimento, Warley Marcos; Silva, Patrícia Pereira da (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the resistance of chickpea (Cicer arietinum) genotypes to the root-knot (Meloidogyne javanica) and root-lesion (Pratylenchus brachyurus) nematodes, as well as to verify how these species affect this crop in field conditions. The experiment was carried out in the Cerrado biome in the state of Goiás, Brazil, in a naturally infested area. The BRS Aleppo, Cícero, BRS Cristalino, BRS Toro, and BRS Kalifa cultivars and the Jamu 96 genotype were evaluated. The assessed variables were: nematode reproduction factor, fresh mass of the aerial part of the plant and of the root system, dry matter of the aerial part of the plant, total dry matter of the plants, chlorophyll index, height of the plants, and grain yield. Pratylenchus brachyurus multiplies more than M. javanica, decreasing root fresh matter, plant height, and grain yield. All genotypes are resistant to M. javanica, especially Jamu 96 and cultivar BRS Kalifa. Jamu 96 and cultivar Cícero are susceptible to P. brachyurus. BRS Kalifa is the cultivar most resistant to both nematodes and shows the highest grain yield.